PERANAN PUPUK ORGANIK CAIR TERHADAP KUALITAS HIJAUAN PAKAN TERNAK (HPT) ASAL TANAMAN PADI RATOON - Jamilah Munir; Sri Mulyani; Yusnaweti Yusnaweti (Universitas Djuanda Bogor, 2019)
The research had been done in Nagari Ikur Lubuk Padang Panjang East District, Padang PanjangCity, with a height of 720 m above sea level. The experiments were conducted on March 2017-July2017. The aimed of this research was to obtain the best variety of rice and liquid organic fertilizerto produce a good forage feed. The experiments were arranged in a split-plot, the main plot beingthe rice crop; Cisokan and Pandan Wangi. The subplot consists of three types of organic liquidfertilizer (OLF), namely; Crocober Plus, Unitas Super, and NASA Commercial LOF replicate 3times to 18 plots. Forage pruning was done at 30 days after cutting ratoon. The data obtainedwere analyzed by F test 5% real level, if the treatment had real effect followed by SignificantDifference (LSD) test 5% real level. The included proximate analysis, digestibility of crudeprotein, fat, crude fiber, organic matter, dry matter, acid detergent fiber (ADF), neutral detergentfiber (NDF), hemicellulose, cellulose, and an extract substance without nitrogen. The results canbe concluded that the Pandan Wangi rice is able to produce the highest fresh weight of forage feedif given by 10% OLF of a Unitas Super.Keywords: Cisokan, forage animal feed, organic liquid fertilizer, Pandan Wangi, ratoon rice crop